WORLD MARKET CONDITIONS, GOVERNMENT POLICY AND THE COCONUT INDUSTRY IN THE PHILIPPINES - Eric L. Hyman, Ph. D (International Coconut Community Journal, 1990)
The Philippines has the largest planted area of coconuts in the world and this crop provides a significant amount of income and employment for smallholders and landless laborers. Nearly all of the coconut harvested is converted into copra for subsequent processing. The bulk of production is exported as crude coconut oil for industrial uses and copra cake for animal feed. Most of the rest goes into refined, edible oil for the domestic market. The industry is subject to major oscillations in supply and demand from year to year. Production is dominated by large‑scale firms currently operating at a low capacity use rate. Real prices may trend downward in the long run due to expanded production from an expansion in the planted area and greater reliance on high‑yield varieties, substitution of other oils, and trade policies of importing countries.